Pengaruh Kepemilikan Manajerial, Kepemilikan Publik, Profitabilitas (ROA), Profitabilitas (ROA), Tingkat Levarage (DER) terhadap Pengungkapan Informasi Sosial Perusahaan (CSR) - Duni Duni; Farkhan Faizal Aldhy (STES Islamic Village, 2020)
The Influence of Managerial Ownership (MAN), Public Ownership, Profitability (ROA), Leverage Level (DER), on Corporate Social Information Disclosure (CSR)” (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange 2011-2015). This research is an empirical study to determine the effect of managerial ownership, public ownership, profitability (ROA), level of leverage (DER), on the disclosure of corporate social information (CSR). The first hypothesis proposed is that the variables of managerial ownership, public ownership, profitability (ROA) and the level of leverage (DER) have a significant positive effect on the CSR disclosure variable, the second hypothesis is that managerial ownership partially has no significant effect. on the disclosure of Corporate Social Responsibility (CSR), the third hypothesis is that public ownership partially has no significant effect on the disclosure of Corporate Social Responsibility (CSR), the fourth hypothesis is Profitability (ROA) partially has a significant positive effect on the disclosure of Corporate Social Responsibility (CSR). , the fifth hypothesis that the level of leverage (DER) partially has no significant effect on the disclosure of Corporate Social Responsibility (CSR). This research was conducted by purposive sampling according to certain criteria that must be met. Of the total population of 133 companies, which met all the requirements and were used as samples in this study, only 7 companies. Some samples were disqualified because they did not meet the predetermined criteria and did not meet the elements of incomplete data.